2019
DOI: 10.32491/jii.v19i2.478
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of Streptococcus agalactiae bacterial vaccine with different coatings for increasing the immunity system on nile tilapia Oreochromis niloticus (Linnaeus, 1758)

Abstract: Vaccination is one of the most effective control measure in preventing Streptococcus agalactiae infection. In this study, vaccine coatings were prepared with certain biomaterials such as chitosan, skim milk, and maltodextrin at concentration 1 % or 10 %, and further freeze-dried. Vaccine selected (in vitro) by tests: viability cell, solubility, protein concentration and protein molecular weight. The result of in vitro test showed that chitosan coating at doses 1 % and 10 % were the best in solubility and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Endapan pelet bakteri kemudian dicuci menggunakan 100 mL phosphate buffer saline (PBS) sebanyak tiga kali dan disentrifugasi pada kecepatan 5.000 rpm selama 15 menit. Endapan pelet kemudian ditambahkan kembali PBS hingga 100 mL dan disimpan pada refrigerator, dan selanjutnya disebut sebagai vaksin sel utuh (Reynalta et al (2018). Vaksin yang telah jadi tersebut selanjutnya diuji viabilitasnya dengan cara ditumbuhkan dengan metode gores cawan pada media NA yang diberi antibiotik rifampisin sebanyak 15 µg L -1 , jika tidak terjadi pertumbuhan bakteri setelah 24 jam pada media tersebut, vaksin aman digunakan (Suprapto et al, 2017).…”
Section: Penyiapan Bakteri Patogen Dan Vaksinunclassified
See 1 more Smart Citation
“…Endapan pelet bakteri kemudian dicuci menggunakan 100 mL phosphate buffer saline (PBS) sebanyak tiga kali dan disentrifugasi pada kecepatan 5.000 rpm selama 15 menit. Endapan pelet kemudian ditambahkan kembali PBS hingga 100 mL dan disimpan pada refrigerator, dan selanjutnya disebut sebagai vaksin sel utuh (Reynalta et al (2018). Vaksin yang telah jadi tersebut selanjutnya diuji viabilitasnya dengan cara ditumbuhkan dengan metode gores cawan pada media NA yang diberi antibiotik rifampisin sebanyak 15 µg L -1 , jika tidak terjadi pertumbuhan bakteri setelah 24 jam pada media tersebut, vaksin aman digunakan (Suprapto et al, 2017).…”
Section: Penyiapan Bakteri Patogen Dan Vaksinunclassified
“…Nilai RPS yang dihasilkan oleh ikan lele menunjukkan bahwa dengan pemberian vaksin dapat meningkatkan respons imun dengan cara membentuk antibodi sehingga ikan lebih tahan terhadap serangan bakteri A.hydrophila pada saat uji tantang. Hal ini selaras dengan Reynalta et al (2018) yang mengatakan bahwa peningkatan kekebalan tubuh pada ikan yang divaksin Tabel 1. Titer antibodi ikan lele yang diberi vaksin dengan metode infiltrasi hiperosmotik Table 1.…”
Section: Relative Percent Survival Dan Tingkat Kelulushidupanunclassified
“…Research and development of vaccines to control S. agalactiae infecting tilapia in Indonesia have been initiated by many research & development agencies and universities, including in different vaccine preparations, doses, and applications. Based on the documentation traced, the development of fish vaccines intended to prevent streptococcosis in tilapia culture in Indonesia has started since the 2010s (Taukhid & Purwaningsih, 2011;Dwinanti et al, 2014;Taukhid et al, 2014;Nisaa et al, 2016;Firdausi et al, 2018;Sukenda et al, 2018;Reynalta et al, 2019;Rahmi et al, 2021;Taukhid et al, 2021) with various results after being subjected to challenge against targeted bacteria.…”
Section: Controlmentioning
confidence: 99%
“…It was concluded that N3M and N4M vaccine strain have better protection as only if it tested with similar bacteria strain (Sukenda et al, 2018). Further studied of streptococcosis vaccine preparation has been done by Reynalta et al (2019) by using different coated vaccine (chitosan, skim milk, and maltodextrin at concentration 1 % or 10 %). The result showed that chitosan coating at doses 1 % and 10 % were the best in solubility and protein concentration test.…”
Section: Controlmentioning
confidence: 99%